Anti-dumping 'to be or not to be' in five acts : a new agenda for research and reform - Broude, Tomer (2003)
Provides a brief outline of the dumping/anti-dumping debate. Demonstrates its focus on domestic welfare. Looks at the global welfare effects of dumping. Questions whether dumping is indeed a problem in international trade. Elaborates on the idea of dumping and anti-dumping as problems of international co-operation in terms of game theory.